Model Pemulihan Psikomotorik dan Kesehatan Mental Anak Usia Dini Pascabencana Hidrometeorologi Berbasis Permainan Tradisional Aceh - Hendra Saputra; Zainatul Hasanah; Wahyudi Wahyudi; Muhammad Rizal (Varied Knowledge Journal, 2026)
This study aims to develop and test the effectiveness of a model for the psychomotor and mental health recovery of young children following a hydrometeorological disaster, based on traditional Acehnese games. The study was conducted in disaster-affected areas of Bireuen Regency, involving young children as research subjects. The approach used was a mixed-methods design combining development and intervention. Data were collected through psychomotor tests, mental health observations, structured observations, and interviews with teachers and parents. The results showed that prior to the intervention, the children tended to exhibit unstable psychological conditions, limited motor activity, and low levels of social interaction. After the intervention, there was a significant improvement in psychomotor skills and mental health, marked by enhanced motor skills, self-confidence, emotional stability, and social interaction abilities. Traditional Acehnese games proved to serve not only as a means of motor stimulation but also as a natural and enjoyable medium for psychological recovery. This study concludes that the developed model is effective and can serve as an alternative strategy for the holistic, post-disaster recovery of young children based on local wisdom.